How Competency Shaped: Implications for Practice With Indonesian Muslims Employee - Zulkifli, Zulkifli (Institut Agama Islam Negeri Kendari, 2022)
This study aims to identify and analyze the factors that determine the work competence of Muslim employees in Indonesia. This research is quantitative research with explorative research. The data collection method in this study was carried out by distributing questionnaires. The analysis method uses Exploratory Factor Analysis (EFA). Based on the results, it is found that three components are formed as factors that determine employee work competence of the 11 indicator items that have been declared feasible for factor testing. These three factors are (1) work capability, (2) religiosity and (3) employee motives. It was found that among the three groups of factors, employee knowledge and skill factors were the dominant factors that determined the work competence of Muslim employees.